Load Insensitive, Low Voltage Quadrature Oscillator Using Single Active Element - Jitendra Mohan; Bhartendu Chaturvedi (Advances in Electrical and Electronic Engineering, 2017)
In this paper, a load insensitive quadrature oscillator using single differential voltage dual-X second generation current conveyor operated at low voltage is proposed. The proposed circuit employs single active element, three grounded resistors and two grounded capacitors. The proposed oscillator offers two load insensitive quadrature current outputs and three quadrature voltage outputs simultaneously. Effects of non-idealities along with the effects of parasitic are further studied. The proposed circuit enjoys the feature of low active and passive sensitivities. Additionally, a resistorless realization of the proposed quadrature oscillator is also explored. Simulation results using PSPICE program on cadence tool using 90 nm Complementary Metal Oxide Semiconductor (CMOS) process parameters confirm the validity and practical utility of the proposed circuit.